CLASSIFICATION AND CHARACTERISATION OF DEEP-WATER SEDIMENT WAVES - Wynn R.B.; Stow D.A.V. (My University, 2002)
Deep-water sediment waves can be classified using a combination of grain size and wave-forming process, although in some cases one or other of these criteria may be indeterminable. Sediment waves are generated beneath currents flowing across the seabed, in the form of either downslope-flowing turbidity currents or alongslope-flowing bottom currents. Waves formed by either process show varying characteristics, depending on whether they are constructed of coarse- or fine-grained sediments. Sediment wave studies over the last five decades are reviewed, and clear trends can be discerned. Early descriptive studies in the 1950s and 1960s relied almost exclusively on seismic reflection profiles, and the wave-forming process was often a subject of much debate. In the 1970s and 1980s the quality of sediment wave datasets increased, with sidescan sonar, deep-sea drilling and numerical modelling all applied to sediment wave studies. Consequently, the wave-forming process became more easily identifiable, and models for the growth of bottom current and turbidity current sediment waves were introduced. Most studies from the 1990s onwards have focussed on turbidity current sediment waves, in response to the increasing demand for data from turbidite systems from the hydrocarbon exploration and production industry. Studies of bottom current sediment waves during this period have focussed on the applications to palaeoceanography, in response to the recent boom in climate change studies. The main focus of this paper is the characterisation of both fine- and coarse-grained, turbidity and bottom current sediment waves, including the depositional environment, wave morphology, wave sediments and migration, and the wave-forming process. In addition, criteria for distinguishing between fine-grained bottom current and turbidity current waves are discussed, and also for identifying other wave-like features formed by different processes, such as creep folds. Although in many sediment wave studies the dominant wave-forming process is easy to determine, in others it is likely that a more complex combination of processes has occurred. Further studies should concentrate on methods for identifying these processes and how they interact, and also investigate the exact mechanisms for the initiation and evolution of sediment wave fields.